PENGARUH KUALITAS PELAYANAN, PROMOSI, DAN HARGA TERHADAP KEPUTUSAN PMEBELIAN CARREFOUR (Studi Kasus pada Konsumen Carrefour Srondol) - Farida Anis Said; Apriatni Endang Prihatini (Universitas Diponegoro, 2017)
Purchase decision is an act of consumers to want to buy the product or not. To be able to create a high purchasing decisions, Carrefour needs to consider factors - factors that influence purchase decisions. Quality of service, promotion, and price are the things to consider when consumers make a purchase decision.This research aimed to determine the effect of service quality, promotion, and price on purchase decisions at Carrefour simultaneously or partially. The hypothesis is there are significant quality of service, promotion, and pricing on purchasing decisions simultaneously or partially. This type of research is explanatory research with a population of 100 people Srondol Carrefour consumers. Data were collected through questionnaires with Likert scale measurement. Data analysis method used is correlation, simple and multiple linear regression using SPSS 21.This research concluded the quality of services, promotion and pricing influence on purchase decisions partially or simultan.Variabel service quality has a greater influence than promotions and price.Based on the results of this study concluded that consumer perception of quality of service, promotion, and price is fair. So companies are advised to keep increasing consumer purchasing decisions in terms of quality of service, promotion, and better pricing more in line with expectations and needs of the company, so that consumers will feel satisfied and purchasing decisions will increase.